2018
DOI: 10.1080/1461670x.2018.1467783
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Interpretive Journalism

Abstract: Interpretive journalism is a journalistic style, characterized by reporters expressing their opinion, speculating about the future or explaining why something happened, without referring to verifiable facts or statements from news sources. Previous research upon this phenomenon is rather scattered, and inconclusive about the mechanisms underlying the presence of this journalistic style. This study aims to address both shortcomings by investigating newspaper coverage on coalition negotiations in Belgium. Conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In addition to these tensions stemming from within the beat, broader changes in journalism brought about by digitalization and commercialization also put pressure on the cultural beat from the outside, as interpretive approaches are seeping into other parts of journalism. Several studies show that explanations, judgements, opinions but also emotions have increased across daily news outlets and in political journalism since the mid-end twentieth century (e.g., Salgado and Strömbäck 2012;Barnhurst 2014;Soontjens 2019). While this may not be a completely new trend, it has long been a blind spot in journalism practice and research, because it counters the ideology of objectivity, key to traditional conceptualizations of journalism (Kotišová 2020;Wahl-Jorgensen 2020).…”
Section: The Epistemology Of Cultural Journalismmentioning
confidence: 99%
“…In addition to these tensions stemming from within the beat, broader changes in journalism brought about by digitalization and commercialization also put pressure on the cultural beat from the outside, as interpretive approaches are seeping into other parts of journalism. Several studies show that explanations, judgements, opinions but also emotions have increased across daily news outlets and in political journalism since the mid-end twentieth century (e.g., Salgado and Strömbäck 2012;Barnhurst 2014;Soontjens 2019). While this may not be a completely new trend, it has long been a blind spot in journalism practice and research, because it counters the ideology of objectivity, key to traditional conceptualizations of journalism (Kotišová 2020;Wahl-Jorgensen 2020).…”
Section: The Epistemology Of Cultural Journalismmentioning
confidence: 99%
“…The phenomenon of evolving writing patterns began to change. Because of the advancement of digital technologies, the news writing style has transformed from being primarily descriptive (inverted pyramid) to becoming more interpretive (narrative) (Soontjens, 2019).…”
Section: Inverted Pyramid Versus Narrative News Style Of Writing In Online Journalismmentioning
confidence: 99%
“…Even in the United States, research, notably on political news, has revealed that interpretive journalism (i.e., trivia, entertainment, and opinions) has served as a substitute for reporting and has shifted toward personal and literary forms (Houston, 2008). The use of interpretive journalism in today's news has gradually increased (Soontjens, 2019).…”
Section: Inverted Pyramid Versus Narrative News Style Of Writing In Online Journalismmentioning
confidence: 99%
“…The effect is substantial; elite outlets score on average 13 per cent higher (more hostile) on the 11-point scale. One explanation might be that elite outlets generally have more extensive coverage on political issues, which allows for more (critical) journalistic interpretation (see Soontjens 2019). The same argument applies to newspaper coverage as opposed to television news reports; the latter is perceived as significantly less hostile.…”
Section: [Insert Figure 1]mentioning
confidence: 99%